Beware of Numbers (and Unsupported Claims of Judicial Bias) - Harry T. Edwards; Linda Elliott (Washington University Law Quarterly, 2002)
In a recent set of articles, Professor Kevin Clermont and Professor Theodore Eisenberg advance the claim that federal appellate judges harbor an unprincipled bias against plaintiff/appellants. The line of reasoning that the authors follow to reach this conclusion is, in our view, quite extraordinary. They first point to data that they claim show that defendants are more likely than plaintiffs to secure reversals in appeals from judgments and verdicts in federal civil cases. They next assert that appellate judges perceive trial courts, especially juries, to be biased in favor of plaintiffs. And, finally, they speculate that, in an effort to overcome the perceived pro-plaintiff bias in the trial courts, appellate judges routinely favor defendants on appeal. The authors dub their conclusion the “anti-plaintiff effect” in federal appellate civil litigation. This thesis is specious, because it is founded on flawed reasoning and deficient empirical research.
Keywords: Bias (Law); Judicial statistics; Social science research; Appellate judges; Appeals (Law); Appellate courts; Federal courts; Judicial ethics; Judicial misconduct